Resistance of cruciferous crops to turnip root fly - Ruuth, Per (Agricultural and Food Science, 1988)
Cruciferous crops have been investigated for resistance to turnip root fly (Delia floralis Fallén) in northern Sweden. Resistance variation has been demonstrated in field trials by observations of wilting symptoms, differences in green mass yield, root damages, surviving plants and number of eggs. Laboratory methods for resistance studies and plant selections in controlled environment are presented, and a method for rearing of flies is described. The definitions of antixenosis, antibiosis and tolerance are discussed, and suggestions for resistance breeding presented. Tutkimuksen kohteena on ollut 15 ristikukkaislajin kestävyys isokaalikärpästä (Delia floralis Fallén) vastaan Pohjois-Ruotsissa. Kestävyyden muuntelu on kenttäkokeissa esiintynyt lakastumissymptomeina, eroina vihreän massan tuotossa, juurivioituksissa, elävänä selviävien kasvien ja munien lukumäärissä. Artikkelissa esitellään kestävyystutkimuksen laboratoriomenetelmiä, valintaa valvotuissa olosuhteissa ja kärpästen kasvatuskeino. Tarkastelussa määritellään käsitteet antixenoosi, antibioosi ja toleranssi ja tehdään ehdotuksia kestävyysjalostuksen suorittamiseksi.